Poland : a partner for developing countries (ITC GenevaCH, 1995)
Discusses Polish foreign trade structure and surveys import trends and prospects for product groups of interest to developing countries. Reviews Polish exports and market prospects in developing countries, and discusses foreign investment.
DC